Research Performance of National Institutes of Technology (NITS) of India During 2001-2010: A Bibliometric Analysis - Bala, Adarsh; Kumari, Santosh (Journal of Information and Knowledge, 2013)
This study analyses the research performance of National Institutes of Technology (NITs) of India during 2001-2010 on several parameters including NITs overall contribution, its growth pattern, citation impact, the share of international collaboration, identification of significant participating countries in NITs international collaboration, contribution and impact by different subject areas, identification of weak and strong subject areas, productivity and impact of prolific authors, pattern of communication of NITs output in most productive journals and characteristics of high cited papers of NITs. The Scopus Citation Database has been used to retrieve the data for 10 years (2001-10).